Evaluation of Oral Microflora-Related to Dental Caries and Salivary pH in type II Diabetic Patients - Murali C.R; Ajithkumar Muthuraj; Anjali Arutchelvan; JothiPriya DanPasko; Vikraman Sethuraman (Wolters Kluwer Medknow Publications, 2024)
BackgroundDiabetes mellitus is one of the chronic diseases and a group of metabolic disorders characterized by a high blood sugar level over a prolonged period. The present study aimed to evaluate and correlate HbA1c, salivary pH, and oral bacterial microflora (streptococcus and lactobacillus colony-forming unit (CFU)) related to dental caries in normal, controlled, and uncontrolled type II diabetic patients. Materials and MethodsA total of 90 samples were taken for this study. The HbA1c test was recorded and grouped into three (normal, prediabetic, and diabetic). CFUs (streptococcus and lactobacillus) were evaluated by the spit-and-swab method. Salivary pH was measured with a pH strip with color coding. By using the post hoc test, the P-value was significant. ResultsThe CFU of streptococcus and lactobacillus in the saliva spit and swab method is statistically significant for P <0.005 and P <0.01 among normal, prediabetic, and diabetic groups. In diabetic patients, there is a higher incidence of dental caries (s.d. 6.7), a higher CFU (s.d. 6194.5) in the bacterial microflora, and a lower salivary pH (s.d. 0.6) than in prediabetic and normal patients. ConclusionFrom the present study, we conclude that there is a slight increase in the CFU of Streptococcus mutans in diabetic patients compared to non-diabetic patients. This CFU increase and decrease in salivary PH were strongly associated with increased dental caries in diabetic patients.